2016
DOI: 10.1155/2016/5808372
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation on Corrosion Effect on Mechanical Properties of Buried Metal Pipes

Abstract: Corrosion has been found to be the most predominant cause for failures of buried metal pipes. A review of published literature on pipe corrosion reveals that little research has been undertaken on the effect of corrosion on mechanical properties of pipe materials and almost no research has been conducted on corrosion effect on fracture toughness. The intention of this paper is to present a comprehensive test program designed to investigate the effect of corrosion on mechanical properties of metals in soil. Two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 15 publications
1
32
0
1
Order By: Relevance
“…Corrosion and chemical degradation deteriorates pipes and affects their material integrity through pipe wall thinning, and functional integrity through pipe displacement affecting joints (Vreeburg et al, 2013). Chemical degradation of metal pipes is well documented (Babovic et al, 2002;Folkman, 2018;Hou et al, 2016;Makar et al, 2001;Rajani and Tesfamariam, 2004;Wasim et al, 2018) and rates of failures vary between geographic region. For example Folkman's (2018) US study found that 28% of all pipe failures were caused by corrosion, with iron pipes having the highest failure rate, whilst Babovic et al, (2002) found 48% of iron pipe failures in a study in Denmark were a result of corrosion.…”
Section: Corrosion and Chemical Degradationmentioning
confidence: 99%
“…Corrosion and chemical degradation deteriorates pipes and affects their material integrity through pipe wall thinning, and functional integrity through pipe displacement affecting joints (Vreeburg et al, 2013). Chemical degradation of metal pipes is well documented (Babovic et al, 2002;Folkman, 2018;Hou et al, 2016;Makar et al, 2001;Rajani and Tesfamariam, 2004;Wasim et al, 2018) and rates of failures vary between geographic region. For example Folkman's (2018) US study found that 28% of all pipe failures were caused by corrosion, with iron pipes having the highest failure rate, whilst Babovic et al, (2002) found 48% of iron pipe failures in a study in Denmark were a result of corrosion.…”
Section: Corrosion and Chemical Degradationmentioning
confidence: 99%
“…The effect of corrosion on fatigue properties, on the other hand, is far more influential. It can be translated into S-N curves obtained from pre-corroded specimens as described in related researches (17)(18)(19)(20). A timedependent interpolation between S-N curves in absence and presence of different degrees of corrosion then allows to describe the coupled effect of corrosion and fatigue.…”
Section: Theoretical Modelmentioning
confidence: 99%
“…The analysis of the cases of pipelines premature failure indicates that one of the main reasons of their destruction is the impact of corrosion [11], including electrocorrosion [12]. One of the ways to increase the service life of pipeline systems is via both external and internal reinforcement of a pipeline with polymer composite materials, most importantly fiberglass.…”
Section: Introductionmentioning
confidence: 99%